Primary structure of an amyloid prealbumin and its plasma precursor in a heredofamilial polyneuropathy of Swedish origin. - Dwulet, F E (1984)
Prealbumin from an individual with heredofamilial amyloid polyneuropathy of Swedish origin was isolated from plasma by using a three-step procedure involving ion exchange, Affi-gel Blue affinity chromatography, and gel filtration. This prealbumin and its associated amyloid fibril subunit protein were digested with trypsin and the resulting peptides were separated by high performance liquid chromatography. Comparison with normal prealbumin peptides showed that an amino acid substitution of a methionine for a valine had occurred at position 30. In the plasma prealbumin, the abnormal residue accounted for 1/3rd of the material while in the amyloid fibrils it accounted for 2/3rds. From this sequence information and the known three-dimensional structure of the prealbumin molecule, a mechanism for the amyloid formation is proposed. It involves formation of the amyloid fibrils by addition of prealbumin dimers or tetramers to the aggregate. Each dimer must contain at least one variant peptide chain while the tetramer must contain at least two abnormal chains. Either of these models can account for the observed amount of normal prealbumin in amyloid fibrils. No proteolytic processing of this molecule is required because the entire undegraded prealbumin molecule is found in the fibrils.